Thematic trends in monographs and the initial training proposal for a degree Course in Chemistry (Research, Society and Development, 2020)
This research aims to identify tendencies in the themes of the monographs presented by undergraduate Chemistry students at the Centro Universitário Norte do Espírito Santo, campus of the Federal University of Espírito Santo, between the periods from 2014 to 2018, analyzing them in the light of the course’s initial training proposal. Methodologically, the work was carried out by means of documentary analysis, configuring itself as a quali-quantitative research of a descriptive nature. To obtain the data, 25 monographs, the Pedagogical Project for the Chemistry course, the course curriculum and course menus were analyzed. The results show that 64% of the monographs fit in the category of Science / Chemistry Education with emphasis on the thematic line of “processes, resources and educational materials” presenting the largest number of works produced. The remaining 36% are works that follow the category of Scientific Research in the area of Chemistry, highlighting the “Organic Chemistry” area in quantity of production. When analyzing the tendencies of the monographs, it was found that they are aligned with the initial training proposal foreseen for the course. It is understood that the tendencies of monographic productions have their aspects rooted in the culture and also reflect the characteristics of the initial training received by graduates.